The LHCspin project - Pappalardo, L. L.; Carassiti, V.; Di Nezza, P.; Ciullo, G.; Lenisa, P.; Steffens, Erhard; Vasilyev, A. (Proceedings of Science, 2019)
The LHCspin project aims to bring both unpolarized and polarized physics at the LHC through the installation of a gaseous fixed target at the upstream end of the LHCb detector. The forward geometry of the LHCb spectrometer (2 < η < 5) is perfectly suited for the reconstruction of particles produced in fixed-target collisions. The fixed-target configuration, with center-of-mass energies ranging from √sNN = 72 GeV in collisions with Pb beams to √s = 115 GeV in pp interactions, allows to cover a wide backward center-of-mass rapidity region, corresponding to the poorly explored high x-Bjorken and high x-Feynman regimes. The project has several ambitious goals regarding heavy-ion physics and new-era quantitative searches in QCD through the study of the nucleon's internal dynamics in terms of both quarks and gluons degrees of freedom. In particular, the use of transversely polarized H and D targets will allow to study the quarks TMDs in pp collisions at unique kinematic conditions. Furthermore, being LHCb specifically designed for heavy-flavor physics, final states with c- or b-quarks (e.g. inclusive quarkonia production) will be efficiently reconstructed, thus providing, among other fundamental measurememnts, access to the so-far unknown gluons TMDs. The status of the project is presented along with a selection of physics opportunities.
CRIS-Team Scopus Importer:2019-12-24